Commit to a credible path of rising CO₂ prices - Sweder van Wijnbergen; Rick van der Ploeg; Stan Olijslagers (Tinbergen Institute, 2020)
CO2 pricing is essential for an efficient transition to the green economy. Despite Daniel, Litterman and Wagner (2019)â exteuro™ claim that CO2 prices should decline, CO2 prices should rise over time. First, damages from global warming are proportional to economic activity and this makes CO2 prices grow at the same rate as the economy. Second, even if uncertainty about the damage ratio is gradually resolved over time, this only slows down the price rise. Third, if CCS is allowed for, the optimal CO2 price will rise before it declines but this decline does not occur until more than two centuries ahead. Fourth, damages are likely to be a very convex function of temperature which with rising temperature implies that CO2 prices must grow faster than the economy. Fifth, internalizing the social benefits of learning by doing or a shift towards technical progress in renewable energy production requires a subsidy for renewable energy, not a temporary spike in CO2 prices. Having high CO2 prices upfront is an artefact of failing to separate out renewable energy subsidies from the carbon price. Finally, efficient intertemporal allocation of policy efforts implies that a temperature cap or cap on cumulative emissions requires that CO2 prices must rise at a rate equal to the risk-adjusted interest rate, typically higher than the economic growth rate. Summing up, CO2 prices must rise at a rate at least equal to the economic growth rate and at most to the risk-adjusted interest rate. They should not decline.
Keywords: H23; Q44; Q51; Q54; 330; CO2 prices; risk; damages